Pregabalin bağımlılığı: bibliyometrik bir analiz - Sak, Fatma Gül; Uslu, Esra (Journal of Dependence, 2024)
Objective: Bibliometric analyses allow determining the scientific research profile, revealing the current situation on the subject, and identifying new research areas. Pregabalin addiction is an addiction that has serious consequences for the individual, family and society. For this reason, taking photographs of studies related to this field can be a guide for researchers. In this regard, the aim of the research is to bibliometrically examine publications addressing the issue of pregabalin addiction.Method: The study was conducted in the Web of Science database. The keywords “pregabalin addiction” were used during the screening without any time limit.Results: 150 publications were reached. Their publication dates were between 2003 and 2023, the average age of publication was 4.83, and the annual increase rate was 5%. The most active country was the United States of America, and the journal with the highest number of publications was “Frontiers in Psychiatry.” In addition, “gabapentin, abuse” was the most frequently used, “opioid, drug abuse” were the motor, “withdrawal” was niche, and “pain, substance” were emerging or disappearing themes. Besides, “neuropathic pain” was a basic theme, and “benzodiazepine” showed consistent development.Conclusion: This is the first bibliometric study addressing pregabalin addiction and provided a comprehensive overview of pregabalin addiction over 20 years. From the quantitative perspective, the mean age of the study and the annual growth rate were low, and the number of studies was limited. Qualitative data showed that research topics mostly clustered on pregabalin addiction, addiction potential, abuse and taking with other drugs, and demonstrated a need for studies in addiction prevention, treatment, and rehabilitation.
Keywords: Bibliometric; pregabalin; addiction